A thiophene-derived hexaazatriphenylene (HAT) fluorescent sensor for the selective detection of Ag+ ion. (30th March 2021) - Zhang, Xiang; Fan, Yu; Zhan, Tian-Guang; Qi, Qiao-Yan; Zhao, Xin
Graphical abstract: Highlights: A hexaazatriphenylene (HAT)-based sensor is designed and synthesized. The sensor selectively recognizes Ag + ion with excellent selectivity, reversibility and fast-response. The advantages of the sensor enable it to be capable of serving as a new type of colorimetric and fluorescent chemosensor. Abstract: Herein, by symmetrically merging six thiophene units into the hexaazatriphenylene (HAT) core, a HAT-based sensor (1 ) was designed and synthesized, which was found capable of exhibiting selective recognition of Ag + with detection limit as low as 1.79 × 10 −6 M in chloroform featuring with significant fluorescence "turn-off" property. Through the systematical investigation with UV–Vis absorption, fluorescence spectroscopy and the naked-eye experiments, as well as the 1 H NMR titration and the Job's plot, it was revealed that sensor 1 could complex with Ag + in a stoichiometric ratio of 2:3. We envisage the construction of such a thiophene-derived HAT molecule is conducive to exploring new type of Ag + sensors, and it also will bring potential application in environmental detection.